CD274 (PD-L1) negatively regulates M1 macrophage polarization in ALI/ARDS - Tang, Nana; Yang, Yang; Xie, Yifei; Yang, Guohui; Wang, Qin; Li, Chang; Liu, Zeyi; Huang, Jian-an (Frontiers in Immunology, 2024)
Background: ALI/ ARDS is a serious clinical syndrome characterized by a high mortality rate. The pathophysiological mechanisms underlying ALI /ARDS remain incompletely understood. Considering the crucial role macrophage polarization in the pathogenesis of ALI/ARDS. This study aims to identify key genes associated with both ALI/ARDS and M1 macrophage polarization by bioinformatics and experimental approaches. Methods: Gene expression profiles relevant to ALI were retrieved from the GEO database to identify co-upregulated DEGs. Enrichment analysis by GO and KEGG. PPI networks were constructed to identify hub genes, and differences in immune cell infiltration were subsequently examined. The expression of hub genes in M1 versus M2 macrophages was evaluated using macrophage polarization datasets. The diagnostic utility of CD274 (PD-L1) for ARDS was assessed by ROC analysis in a validation dataset. Experimental confirmation was conducted using two LPS-induced M1 macrophage models and an ALI mouse model. The role of CD274 (PD-L1) in M1 macrophage polarization and associated proinflammatory cytokine production was further investigated by siRNAmediated silencing. Results: A total of 99 co-upregulated DEGs were identified in two ALI-linked datasets. Enrichment analysis revealed that these DEGs were mainly involved in immune-inflammatory pathways. The following top 10 hub genes were identified from the PPI network: IL-6, IL-1B, CXCL10, CD274, CCL2, TLR2, CXCL1, CCL3, IFIT1, and IFIT3. Immune infiltration analysis revealed a significantly increased abundance of M1 and M2 macrophages in lung tissue from the ALI group compared to the control group. Subsequent analysis confirmed that CD274 (PD-L1), a key immunological checkpoint molecule, was highly expressed within M1 macrophages. ROC analysis validated CD274 (PD-L1) as a promising biomarker for the diagnosis of ARDS. Both in vitro and in vivo experiments supported the bioinformatics analysis and confirmed that the JAK-STAT3 pathway promotes CD274 (PD-L1) expression on M1 macrophages. Importantly, knockdown of CD274 (PD-L1) expression potentiated M1 macrophage polarization and enhanced proinflammatory cytokines production.This study demonstrates a significant correlation between CD274 (PD-L1) and M1 macrophages in ALI/ARDS. CD274 (PD-L1) functions as a negative regulator of M1 polarization and the secretion of proinflammatory cytokines in macrophages. These findings suggest potential new targets for the diagnosis and treatment of ALI/ARDS.